Methane and Carbonyl Sulfide Analysis of Siple Dome Ice Core Subsamples - Saltzman, Eric; Aydin, Murat (IEDA: US Antarctic Program Data Center, 2002)
Abstract: This data set is part of the West Antarctic Ice Sheet cores (WAISCORES) project, an NSF-funded project to understand the influence of the West Antarctic ice sheet on climate and sea level change. WAISCORES researchers acquired and analyzed ice cores from the Siple Dome, in the Siple Coast region, West Antarctica. Siple Dome ice cores were analyzed for methanesulfonate (MSA) and carbonyl sulfide (OCS). The methanesulfonate analysis was done on cores A-E and a hot water core, and the carbonyl sulfide analysis was done on 11 C cores. Methanesulfonate data include the sample identification number, depth, and methanesulfonate parts per billion (ppb) of each sample. Carbonyl sulfide data include the depth, OCS parts per trillion (ppt) of each sample, percent error, and gas age (years). Data are available via FTP in tab-delimited ASCII text (.dat, .txt) file format.